Pengaruh Kepemimpinan Melayani Dan Organisasi Pembelajar Melalui Kompetensi terhadap Kinerja Karyawan Pada Perusahaan Pelayaran Jakarta - Handini Salsabila; Edhie Budi Setiawan; Basri Fahriza; Nursery Alfaridi; Prasadja Ricardianto (Dinasti Review, 2025)
XYZ Shipping Company is engaged in the shipping line industry and is responsible for managing vessel scheduling with several shipping agents and internal departments in sea transportation operations. Some employees perceive that the lack of servant leadership practices has an impact on employee performance, thereby requiring further study to assess its influence. This research aims to analyze the effect of servant leadership and learning organization on employee performance through competence as a mediating variable at XYZ Shipping Company in Jakarta. This study uses a quantitative approach with 120 employee respondents. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that servant leadership and learning organization have a significant effect, both directly and indirectly through competence, on employee performance. These findings emphasize the importance of implementing servant leadership to strengthen competence and develop a learning organization culture that contributes to improving employee performance in the maritime transportation sector.